1999
DOI: 10.1192/bjp.175.5.472
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal affective disorder among primary care attenders and a community sample in Aberdeen

Abstract: There is a high prevalence of SAD among patients attending their GPs in January in Aberdeen; this is likely to reflect a similar rate in the community.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 17 publications
1
24
0
Order By: Relevance
“…al. [6] found a prevalence of 5.3% of seasonal affective disorder during the winter months in a primary care population and Thompson et al [1] found a prevalence of 5.6% of seasonal affective disorders in a primary care population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…al. [6] found a prevalence of 5.3% of seasonal affective disorder during the winter months in a primary care population and Thompson et al [1] found a prevalence of 5.6% of seasonal affective disorders in a primary care population.…”
Section: Discussionmentioning
confidence: 99%
“…The most widely used instrument in those studies is the Seasonal Pattern Assessment Questionnaire (SPAQ), a self rating screening questionnaire that retrospectively measures seasonal variation in mood, social activities and atypical depressive symptoms such as increased sleep, increased appetite and weight and a lowered energy level [4]. Female gender and young age have been described to be associated with a higher prevalence of SAD [5,6]. The influence of latitude on the prevalence of SAD has been suggested but could not be demonstrated [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Studies in the UK screening with the SPAQ and fur ther inter viewing using DSM-IV criteria have yielded rates between 2.4 and 3.5 per cent. 5,6 SAD is generally believed to affect women more than men and the age of onset is usually between 20-30 years, although most can recall symptoms from earlier in their life. The ratio discrepancy between the sexes tends to diminish in old age.…”
Section: Characteristics Of Sadmentioning
confidence: 99%
“…More recent studies in the UK, utilising interviews and DSM-IV criteria after screened patients had fulfilled SPAQ criteria for Advances in Psychiatric Treatment (2004), vol. 10. http:/ /apt.rcpsych.org/ winter depression, gave rise to estimated adult community prevalence rates of 3.5% in Aberdeen (Eagles et al, 1999) and 2.4% in North Wales (Michalak et al, 2001).…”
Section: Epidemiology Of Winter Depressionmentioning
confidence: 99%